2023
DOI: 10.3390/nu15153344
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nutrition and Physical Activity on Local and Systemic Inflammatory Signs in Experimentally Induced Gingivitis

Abstract: Although numerous studies have been published investigating the relationship between various dietary components and inflammatory periodontal disease, it has not yet been possible to clearly distinguish between periodontally healthy and unhealthy diets. This clinical study aimed to assess the association of specific food ingredients and physical activity on local and systemic inflammatory signs in experimentally induced gingivitis. Thirty-nine non-smoking periodontally healthy volunteers (mean age 23.2 ± 3.8 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Staufenbiel et al [15] investigated the influence of nutrition and physical activity on the course of experimental gingivitis. They analyzed the data of thirty-nine non-smoking periodontally healthy participants and concluded that both an anti-inflammatory diet (measured with the dietary inflammatory index) and physical activity, or, even better, a combination of both, were able to reduce the amount of bleeding on probing (BOP).…”
mentioning
confidence: 99%
“…Staufenbiel et al [15] investigated the influence of nutrition and physical activity on the course of experimental gingivitis. They analyzed the data of thirty-nine non-smoking periodontally healthy participants and concluded that both an anti-inflammatory diet (measured with the dietary inflammatory index) and physical activity, or, even better, a combination of both, were able to reduce the amount of bleeding on probing (BOP).…”
mentioning
confidence: 99%